“BLOOD IS THICKER THAN WATER” : WHEN THE FOLK TALKS ABOUT ITS LORE: INTERPRETATIONS OF THE PROVERB IN THE BALKANS - Tserpes, George (Proverbium - Yearbook, 2018)
Folkloristics as a discipline is interested in all folklore genres, and of course also in the proverb. However, it is often attempted by the folklorists to collect as many variants as possible, giving thus particular emphasis to quantity. But this seems to ignore the folk. In this article we aim to attempt a metafolkloristic approach for the proverb “blood is thicker than water.” We will try to see how this proverb is interpreted from informants from the Balkan Peninsula in an attempt to bring together the folk with the lore.